Pedological characterization and soil fertility assessment of the selected rice irrigation schemes, Tanzania - Marzouk, Said H.; Tindwa, Hamis J.; Massawe, Boniface H. J.; Amuri, Nyambilila A.; Semoka, Johnson M. (Frontiers in Soil Science, 2023)
Updating soil information is crucial in designing appropriate soil and water management options. This study was conducted to characterize, classify and assess the fertility status of soils in two rice irrigation schemes of Morogoro region in Tanzania. The studied pedons were named MKU-P1 and MKD-P1 for Mkula and Mkindo irrigation schemes, respectively. A total of 7 composite soil samples (0-20cm) were collected for soil fertility assessments. Landform, soil morphological features, parent material, natural vegetation, drainage, erosion, and laboratory data were used to classify the soils in their respective order as per USDA soil taxonomy and WRB soil classification systems. The pedons were sandy clay loam in the topsoil and sandy clay to clay in the subsoil, soil reaction ranged from medium acid (pH 5.7) to strongly alkaline (pH 8.6). The surface soils ranged from very strongly acidic (pH 4.7) to neutral (pH 6.9). Based on the USDA Soil Taxonomy, MKU-P1 is classified as Inceptisols cumulic humaquepts and MKD-P1 as Vertisols Fluvaquentic endoaquerts corresponding to Subaquatic fluvisols (loamic, oxyaquic) and Irragric vertisols (gleyic) in WRB, respectively. These pedons were ranked as suitable for rice production. All soils are deficient in total N, available P, K+, and Ca2+, but with excessive iron and manganese and likely to pose toxicity to crops. It is nutrient application is based on site-specific recommendations and the timing for nitrogen and phosphorus remains important to avoid losses. Salinity in subsurface pedons MKD-P1 needs to be taken into future consideration. Key words : soil fertility, soil classification, paddy soils, pedons